Geriatric Family Support and Diabetic Type-2 Glycemic Control - Shiva Heidari; Maryam Nouri Tajer; Fateme Hosseini; Mehrnoush Inanlou; Fateme Golgiri; Fateme Shirazi (Sālmand, 2008)
Objectives: As the most part of geriatric (65 years and older) diabetic care is given at home, family support has an important role in their blood sugar level control care. This study aimed to assess the relationship between family support and blood sugar level control in such elderly suffering type-2 diabetes.